Tomándose la historia en serio. Danto, esencialismo histórico e indiscernibles - Tozzi, Veronica (Revista de Filosofía, 2008)
The place that Arthur Danto gives to history, as constitutive to as and our world, as well as a discipline able to produce knowledge of the past, reach its cenit with his philosophy of art. In “the End of Art”, Danto announces an end of the history of the search of the philosophical definition of art and the beginning of the era of pluralism. It is in this account where essencialism and historicism are combined in a way that estimules a heat debate that continues today. In this paper, I give a reconstruction of Danto’s Philosophy of historical language in order to show why this combination is possible and which compromises that should be assumed by an authentic historicism.